Diasporic and Transnational Communication: Technologies, Policies and Regulation - Verhulst, Stefaan (Javnost-The Public, 1999)
New communications technologies are a key element of the increased capacity of diasporic and transnational communities to develop effective networks. Little comparative work has been carried out or published on the use of such communications technologies as part of emerging transnationalism and virtually no work has been done on comparing patterns of policy, law and regulation as .enablers. or .disablers. of these new networks or reactions on the part of nation-states to these patterns. In this issue, we seek to use an interdisciplinary approach a prerequisite for research into the dynamics of diasporic communities . to assess the role of communications flow and regulation as, on the one hand, a catalyst for contemporary globalisation processes, and, on the other, as a response to perceived threats to the existing order from bottom-up challenges posed by global community networks.